Earthquake Risk Management on a Community Level - A Case Study of Bhaktapur Durbar Square - Phaiju, Libas; Shrestha, Rameswor; Shah, Suraj (Journal of Science and Engineering, 2019)
Earthquake is a natural hazard which when it happens turn out to be disaster that kill thousands of people and cause devastation of cities and villages within 30-60 seconds. Natural disaster may cause large economic impact and impeded socioeconomic development. Virtually the entire population of Nepal is at risk of natural hazards. Earthquake interrupts the proper functioning of the community causing socio-cultural and economic imbalances and losses which results very hard situation to sustain life with available resources. Due to its location on a tectonic active zone Nepal has a long history of earthquake activities of smaller and greater magnitude which are an inevitable part of Kathmandu valley as well. The Statement of problem in research (based on field survey 2067) was about different socio-economic and development activities induced by people or community which made their buildings and places defenceless during natural hazard like earthquake. The research focused on earthquake risk and its management at community level by identifying, analysing and mitigating the vulnerability of the people, place and buildings at Bhaktapur Durbar Square area through physical and social vulnerability studies and was limited to study of earthquake risk management through rapid visual assessment and analysis. The study area that lies in the world heritage site is vulnerable to earthquake risk not only due to different socio economic and development activities but also due to inaction from concerned authorities. So; the earthquake risk can be mitigated through community level earthquake risk management as it is the most effective and sustainable.